PERBANDINGAN PERFORMA DUA STRAIN AYAM JANTAN TIPE MEDIUM YANG DIBERI RANSUM KOMERSIAL BROILER - Fazar Ardiansyah; Syahrio Tantalo; Khaira Nova (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
This study aims to determine the best strain of the performance of medium type roosters fed commercial broiler rations.  This study conducted for 7 weeks from 19 may to 06   july 2012, in the chicken coop department of animal husbandry, faculty of agriculture, University of  Lampung. The chicken is a rooster who used medium type strain Isa Brown and  Lohman each as much as 100  individuals.  This study compared two treatments are different strains rooster medium type  Isa Brown rooster and Lohman medium type srtain. Data obtained from the study were analyzed using student t-test on the real level of 5%.  The variables measured were ration consumpion, body weight gain, conversion ratio, and income over feed cost (IOFC).  The results showed that the strain Isa Brown had ration consumption  and body weight were significantly (P<0.05) higher than Lohman strain, but the conversion ratio and the type of medium IOFC cock  both strains were not significantly (P>0.05) . Keyword: Performance, strain, roosters medium type, and commercial broiler ration.